A zirconia aerogel-modified lightweight heat-insulating fiber preform and its preparation method

By introducing crosslinking agent, pore structure control agent and drying control agent into the precursor of zirconium dioxide aerogel, and using liquid alkanes for solvent replacement, the problems of large shrinkage and poor stability in the preparation of traditional ZrO2 aerogels are solved. , realizes an efficient and low-cost preparation process, suitable for large-scale production.

CN118771849BActive Publication Date: 2025-02-25HARBIN INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410812386.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2025-02-25
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

In the preparation of traditional ZrO2 aerogels, there are problems such as large shrinkage, poor stability, high molding difficulty and high cost, and they are not suitable for large-scale production.

Method used

By introducing crosslinking agent, pore structure control agent and drying control agent into the zirconium dioxide aerogel precursor, and using liquid alkanes as replacement solvent for solvent replacement, the Zr-O skeleton is strengthened and the problem of skeleton shrinkage during drying is improved during the drying process. , realize normal pressure drying.

Benefits of technology

It solves the problems of large shrinkage, poor stability, high molding difficulty and high cost in the preparation of traditional ZrO2 aerogels. It is suitable for mass production. The modified fiber preform has excellent antioxidant properties and structural stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118771849B_ABST
    Figure CN118771849B_ABST
Patent Text Reader

Abstract

The present invention provides a zirconia aerogel-modified lightweight heat-insulating fiber preform and a preparation method thereof, which belongs to the field of heat-insulating composite materials. The preparation method of the zirconia aerogel-modified lightweight heat-insulating fiber preform comprises the following steps: mixing a zirconium compound, a solvent, a pH regulator, a cross-linking agent, a pore structure control agent and a drying control agent to obtain a zirconium dioxide aerogel precursor solution; immersing the fiber preform in the zirconium dioxide aerogel precursor solution and adding a gel accelerator, and obtaining a zirconia aerogel-modified lightweight heat-insulating fiber preform through gel reaction, solvent replacement, drying and heat treatment. The preparation method of the zirconia aerogel-modified fiber preform provided by the present invention solves the problems of large shrinkage, poor stability, high molding difficulty and high cost in the preparation of traditional ZrO2 aerogels, and is suitable for mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heat-insulating composite materials, and in particular to a zirconia aerogel-modified lightweight heat-insulating fiber preform and its preparation method. Background Art

[0002] Traditional ablation-type thermal protection materials are widely used in various thermal protection structures due to their excellent thermal insulation properties. However, with increasingly stringent service requirements, more demanding requirements are being placed on the temperature resistance, durability, and reliability of these materials.

[0003] Existing technologies utilize a sol-gel process to form an aerogel protective layer on the fiber surface, achieving both antioxidant protection and thermal insulation properties for the fiber preform. ZrO2 ceramics have a melting point exceeding 2000℃, exhibiting excellent high-temperature resistance. ZrO2 aerogels, with their porous structure, possess both high-temperature resistance, antioxidant properties, and thermal insulation. However, due to their low skeletal strength, they are prone to shrinkage and damage during preparation, increasing the difficulty of production. Currently, supercritical drying and freeze-drying are mainly used to address these issues, but these methods are not suitable for mass production. Furthermore, the preparation of composite multi-component aerogels has also addressed these problems to some extent, but the introduction of other components can negatively impact the structure and properties of the ZrO2 aerogel. Summary of the Invention

[0004] To address one or more technical problems existing in the prior art, this invention provides a lightweight heat-insulating fiber preform modified with zirconia aerogel and its preparation method. The preparation method of the zirconia aerogel-modified fiber preform provided by this invention solves the problems of large shrinkage, poor stability, high molding difficulty and high cost in the traditional ZrO2 aerogel preparation, and is suitable for mass production. The microstructure of the fibers in the modified fiber preform is not damaged, the ZrO2 aerogel uniformly coats the fibers, and the room temperature thermal conductivity does not change significantly, exhibiting excellent antioxidant properties and structural stability.

[0005] In a first aspect, this invention provides a method for preparing a lightweight, heat-insulating fiber preform modified with zirconia aerogel, the method comprising the following steps:

[0006] A zirconium compound, solvent, pH adjuster, crosslinking agent, pore structure control agent, and drying control agent are mixed to obtain a zirconium dioxide aerogel precursor solution; the crosslinking agent is a silane coupling agent; the pore structure control agent is polyethylene glycol; and the drying control agent is one or more of acetamide, N,N-dimethylformamide, ethylene glycol, and oxalic acid.

[0007] The fiber preform is impregnated in the zirconia aerogel precursor solution and a gelation accelerator is added. After gelation reaction, solvent replacement, drying and heat treatment, a zirconia aerogel modified lightweight heat-insulating fiber preform is obtained; the solvent replacement solvent is a liquid alkane.

[0008] Preferably, the zirconium compound is one or more selected from zirconium oxychloride octahydrate, zirconium oxynitrate, zirconium n-butoxide, zirconium tetrachloride, and zirconium polyacetylacetonate.

[0009] The mass ratio of the solvent to the zirconium precursor is 5–10:1–5; preferably, the solvent is an alcohol, preferably one or more of anhydrous ethanol, propanol, methanol, and ethylene glycol; and / or

[0010] The amount of the pH adjuster is 40-60% of the mass of the zirconium compound; preferably, the pH adjuster is an organic weak acid or a mixture containing inorganic acid and alkaline substances.

[0011] Preferably, the molar ratio of the crosslinking agent to the zirconium compound is 0.1 to 1:1; more preferably, the crosslinking agent is one or more of methyltrimethoxysilane, dimethyldiethoxysilane, γ-aminopropyltriethoxysilane, and γ-glycidoxypropyltrimethoxysilane.

[0012] Preferably, the molar ratio of the pore structure control agent to the zirconium compound is 0.1-0.5:1-5; more preferably, the pore structure control agent is one or more of polyethylene glycol 400, polyethylene glycol 600, and polyethylene glycol 1000.

[0013] Preferably, the molar ratio of the drying control agent to the zirconium compound is 0.1–1:1–5.

[0014] Preferably, the fiber preform uses one or more of the following fibers: carbon fiber, quartz fiber, glass fiber, mullite fiber, and phenolic fiber; and / or

[0015] The fiber preform is one or more of the following: continuous fiber needle-punched structure, mesh structure, 2.5D braided structure, and three-dimensional braided structure.

[0016] Preferably, the molar ratio of the gelation accelerator to the zirconium compound is 1 to 10:1; more preferably, the gelation accelerator is one or more of polyacrylic acid, urea, and citric acid.

[0017] Preferably, the temperature of the gelation reaction is 60–90°C; and / or

[0018] The temperature of the solvent replacement is not higher than the boiling point of the liquid alkane; preferably, the boiling point of the liquid alkane is not higher than 100°C.

[0019] Preferably, the drying is one or more of atmospheric pressure drying and supercritical drying; and / or

[0020] The heat treatment involves heating the temperature to 600–1200°C at a rate of 4–10°C / min and holding it at that temperature for 1.5–3.5 hours.

[0021] In a second aspect, the present invention provides a zirconia aerogel-modified lightweight heat-insulating fiber preform, which is prepared by the preparation method described in the first aspect.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] This invention first mixes a zirconium compound, a solvent, a pH adjuster, a crosslinking agent, a pore structure control agent, and a drying control agent to obtain a zirconium dioxide aerogel precursor solution. The pH adjuster is used to regulate the pH of the precursor solution to control the hydrolysis process of the zirconium compound. A silane coupling agent-type crosslinking agent promotes the hydrolysis and crosslinking reactions of the zirconium compound, while simultaneously introducing an appropriate amount of Si-O framework into the Zr-O framework to strengthen the original Zr-O framework, creating the possibility for atmospheric pressure drying. This ensures that the original aerogel structure is maintained after high-temperature treatment, overcoming the problem that the monomer reactivity of the zirconium compound after hydrolysis is low, resulting in a low degree of crosslinking and a weak Zr-O framework, making the aerogel structure prone to damage during atmospheric pressure drying and high-temperature treatment. The pore structure control agent, which does not participate in the hydrolysis and crosslinking reactions, helps to form and control the micro-nano porous structure of the aerogel framework. By occupying spaces in the pores in solution form, it limits the framework shrinkage of the aerogel during drying, overcoming the problem of material damage caused by framework shrinkage. A drying control agent that does not participate in hydrolysis and cross-linking reactions inhibits the growth of gel particles by limiting the cross-linking reaction of zirconium monomers, resulting in a more uniform pore size distribution in the gel. This significantly reduces uneven stress distribution during drying and effectively overcomes the problem of stress concentration leading to gel skeleton destruction and failure to dry and form. The fiber preform is then impregnated in a zirconium dioxide aerogel precursor solution, and a gelation promoter is added to facilitate gel formation. Low-boiling-point liquid alkanes are then used as a solvent for solvent replacement. The low surface tension and interaction force between alkanes and the skeleton prevent solvent evaporation from damaging the skeleton during drying. Finally, heat treatment removes organic components from the aerogel while maintaining its structure, yielding a zirconium dioxide aerogel-modified lightweight heat-insulating fiber preform. Compared to traditional zirconium dioxide aerogel preparation processes, the zirconium dioxide aerogel-modified lightweight heat-insulating fiber preform preparation process provided by this invention is simpler, more efficient, lower in cost, and more stable, making it suitable for mass production.

[0024] This invention introduces a crosslinking agent, a pore structure control agent, and a drying control agent into the zirconium dioxide aerogel precursor solution. After gelation, liquid alkanes are used as a displacement solvent for solvent replacement, strengthening the Zr-O skeleton. This effectively improves the problem of skeleton shrinkage during drying and allows for atmospheric pressure drying. It solves the problems of high shrinkage, poor stability, high molding difficulty, and high cost in traditional ZrO2 aerogel preparation, making it suitable for mass production. Compared with the unmodified fiber preform, the modified fiber preform shows no damage to the microstructure of the fibers. The ZrO2 aerogel uniformly coats the fibers, with a density increase of no more than 32%, and no significant change in room temperature thermal conductivity, exhibiting excellent antioxidant properties and structural stability. The residual weight after heating to 1000℃ in an argon atmosphere exceeds 97%; the residual weight after heating to 1000℃ in an air atmosphere is not less than 96%. Attached Figure Description

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 This is a scanning electron microscope image of a zirconia aerogel-modified lightweight heat-insulating fiber preform before (left) and after (right) modification, provided by the present invention.

[0027] Figure 2 The TG curve of the zirconia aerogel-modified lightweight heat-insulating fiber preform provided in Embodiment 1 of the present invention in an air atmosphere;

[0028] Figure 3 This is a scanning electron microscope image of the modified lightweight heat-insulating fiber preform provided in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0030] In a first aspect, this invention provides a method for preparing a lightweight, heat-insulating fiber preform modified with zirconia aerogel, the method comprising the following steps:

[0031] A zirconium compound, solvent, pH adjuster, crosslinking agent, pore structure control agent, and drying control agent are mixed to obtain a zirconium dioxide aerogel precursor solution; the crosslinking agent is a silane coupling agent; the pore structure control agent is polyethylene glycol; and the drying control agent is one or more of acetamide, N,N-dimethylformamide, ethylene glycol, and oxalic acid.

[0032] The fiber preform is impregnated in the zirconia aerogel precursor solution and a gelation accelerator is added. After gelation reaction, solvent replacement, drying and heat treatment, a zirconia aerogel modified lightweight heat-insulating fiber preform is obtained; the solvent replacement solvent is a liquid alkane.

[0033] This invention first mixes a zirconium compound, a solvent, a pH adjuster, a crosslinking agent, a pore structure control agent, and a drying control agent to obtain a zirconium dioxide aerogel precursor solution. The pH adjuster is used to regulate the pH of the precursor solution to control the hydrolysis process of the zirconium compound. A silane coupling agent-type crosslinking agent promotes the hydrolysis and crosslinking reactions of the zirconium compound, while simultaneously introducing an appropriate amount of Si-O framework into the Zr-O framework to strengthen the original Zr-O framework, creating the possibility for atmospheric pressure drying. This ensures that the original aerogel structure is maintained after high-temperature treatment, overcoming the problem that the monomer reactivity of the zirconium compound after hydrolysis is low, resulting in a low degree of crosslinking and a weak Zr-O framework, making the aerogel structure prone to damage during atmospheric pressure drying and high-temperature treatment. The pore structure control agent, which does not participate in the hydrolysis and crosslinking reactions, helps to form and control the micro-nano porous structure of the aerogel framework. By occupying spaces in the pores in solution form, it limits the framework shrinkage of the aerogel during drying, overcoming the problem of material damage caused by framework shrinkage. A drying control agent that does not participate in hydrolysis and cross-linking reactions inhibits the growth of gel particles by limiting the cross-linking reaction of zirconium monomers, resulting in a more uniform pore size distribution in the gel. This significantly reduces uneven stress distribution during drying and effectively overcomes the problem of stress concentration leading to gel skeleton destruction and failure to dry and form. The fiber preform is then impregnated in a zirconium dioxide aerogel precursor solution, and a gelation promoter is added to facilitate gel formation. Low-boiling-point liquid alkanes are then used as a solvent for solvent replacement. The low surface tension and interaction force between alkanes and the skeleton prevent solvent evaporation from damaging the skeleton during drying. Finally, heat treatment removes organic components from the aerogel while maintaining its structure, yielding a zirconium dioxide aerogel-modified lightweight heat-insulating fiber preform. Compared to traditional zirconium dioxide aerogel preparation processes, the zirconium dioxide aerogel-modified lightweight heat-insulating fiber preform preparation process provided by this invention is simpler, more efficient, lower in cost, and more stable, making it suitable for mass production.

[0034] This invention introduces a crosslinking agent, a pore structure control agent, and a drying control agent into the zirconium dioxide aerogel precursor solution. After gelation, liquid alkanes are used as a displacement solvent for solvent replacement, strengthening the Zr-O skeleton. This effectively improves the problem of skeleton shrinkage during drying and allows for atmospheric pressure drying. It solves the problems of high shrinkage, poor stability, high molding difficulty, and high cost in traditional ZrO2 aerogel preparation, making it suitable for mass production. Compared with the unmodified fiber preform, the modified fiber preform shows no damage to the microstructure of the fibers. The ZrO2 aerogel uniformly coats the fibers, with a density increase of no more than 32%, and no significant change in room temperature thermal conductivity, exhibiting excellent antioxidant properties and structural stability. The residual weight after heating to 1000℃ in an argon atmosphere exceeds 97%; the residual weight after heating to 1000℃ in an air atmosphere is not less than 96%.

[0035] According to some preferred embodiments, the zirconium dioxide aerogel precursor solution also includes water. The inventors have found that adding an appropriate amount of water is beneficial to promoting the reaction, but the properties of the resulting material are not significantly different from those without water. Therefore, whether or not to add water can be selected according to the actual situation. The mass ratio of zirconium compound, solvent and water is 1-5:5-10:0-2.

[0036] According to some preferred embodiments, the zirconium compound is one or more of zirconium oxychloride octahydrate, zirconium oxynitrate, zirconium n-butoxide, zirconium tetrachloride, and zirconium polyacetylacetonate; the types of zirconium compounds of the present invention include, but are not limited to, the above types.

[0037] According to some preferred embodiments, the mass ratio of the solvent to the zirconium precursor is 5-10:1-5; preferably, the solvent is an alcohol, preferably one or more of anhydrous ethanol, propanol, methanol, and ethylene glycol.

[0038] According to some preferred embodiments, the amount of the pH adjuster is 40-60% of the mass of the zirconium compound; preferably, the pH adjuster is an organic weak acid or a mixture containing an inorganic acid and a basic substance. The organic weak acid is one or more of acetic acid, citric acid, malic acid, oxalic acid, benzoic acid, salicylic acid, and succinic acid; the inorganic acid is one or more of hydrochloric acid, nitric acid, sulfuric acid, and hypochlorous acid; and the basic substance is one or more of hydroxides, carbonates, and bicarbonates. The preparation of the mixture containing the inorganic acid and the basic substance includes adding the inorganic acid and the basic substance to water, respectively, wherein the mass ratio of the acid, the basic substance, and water is 5-10:1:50-100. In this invention, a pH adjuster is used to adjust the pH of the zirconium dioxide aerogel precursor solution to ensure that the pH of the zirconium dioxide aerogel precursor solution is 4.5-8.5.

[0039] According to some preferred embodiments, the molar ratio of the crosslinking agent to the zirconium compound is 0.1 to 1:1 (e.g., 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10); preferably, the crosslinking agent is one or more of methyltrimethoxysilane, dimethyldiethoxysilane, γ-aminopropyltriethoxysilane, and γ-glycidoxypropyltrimethoxysilane.

[0040] This invention promotes the hydrolysis and cross-linking reactions of zirconium compounds by introducing silane coupling agents as cross-linking agents. Simultaneously, it introduces an appropriate amount of Si-O skeleton into the Zr-O framework to strengthen the original Zr-O framework, creating the possibility for atmospheric pressure drying. This overcomes the problem that the low monomer reactivity after zirconium compound hydrolysis leads to a low degree of cross-linking, resulting in a weak Zr-O framework that is easily destroyed during drying. The inventors discovered that when the molar ratio of the cross-linking agent to the zirconium compound is 1–2:1 (excluding 1:1), a ZrO2-SiO2 composite aerogel is formed. The ZrO2 aerogel and SiO2 aerogel form independently, and the resulting frameworks are intertwined. However, the significant differences in their physical properties lead to structural damage at high temperatures. Compared to the ZrO2-SiO2 composite aerogel, the Si-modified ZrO2 aerogel prepared by introducing an appropriate amount of Si-O skeleton into the Zr-O framework exhibits better structural and performance stability. When the amount of crosslinking agent continues to increase (greater than 2:1), Zr-modified SiO2 aerogel is obtained. The main skeleton of the material is Si-O, which has a low melting point. At this time, ZrO2 aerogel will not be able to play its role as a high-temperature ablation-resistant heat insulation agent and protect the fiber preform.

[0041] According to some preferred embodiments, the molar ratio of the pore structure control agent to the zirconium compound is 0.1-0.5:1-5 (e.g., 1:2, 1:4, 1:6, 1:8, 1:10, 1:20, 1:30, 1:40 or 1:50); preferably, the pore structure control agent is one or more of polyethylene glycol 400, polyethylene glycol 600 and polyethylene glycol 1000.

[0042] This invention helps to form and control the micro- and nano-porous structures of the aerogel skeleton by adding a pore structure control agent that does not participate in hydrolysis or cross-linking reactions. By occupying the pores in the form of a solution, it can limit the skeleton shrinkage of the aerogel during the drying process and overcome the problem of material damage caused by skeleton shrinkage.

[0043] According to some preferred embodiments, the molar ratio of the drying control agent to the zirconium compound is 0.1 to 1:1 to 5 (for example, it can be 1:2, 1:4, 1:6, 1:8, 1:10, 1:20, 1:30, 1:40 or 1:50).

[0044] This invention incorporates a drying control agent that does not participate in hydrolysis or cross-linking reactions. By limiting the cross-linking reaction of zirconium monomers, it can inhibit the growth of gel particles, making the pore size distribution of the gel more uniform. This significantly reduces the uneven stress distribution during the drying process and overcomes the problem of stress concentration leading to the destruction of the gel skeleton and failure to dry and form.

[0045] According to some preferred embodiments, the fiber preform uses one or more of the following fibers: carbon fiber, quartz fiber, glass fiber, mullite fiber, and phenolic fiber.

[0046] According to some preferred embodiments, the fiber preform is one or more of the following: continuous fiber needle-punched structure, mesh structure, 2.5D braided structure, and three-dimensional braided structure.

[0047] According to some preferred embodiments, the molar ratio of the gelation accelerator to the zirconium compound is 1 to 10:1 (e.g., 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1); preferably, the gelation accelerator is one or more of polyacrylic acid, urea and citric acid.

[0048] According to some preferred embodiments, the temperature of the gelation reaction is 60-90°C (e.g., 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, or 90°C), and the time is 10-20 hours (e.g., 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, or 20 hours).

[0049] According to some preferred embodiments, the temperature of the solvent replacement is not higher than the boiling point of the liquid alkane; preferably, the boiling point of the liquid alkane is not higher than 100°C.

[0050] According to some preferred embodiments, the drying is one or more of atmospheric pressure drying and supercritical drying.

[0051] According to some preferred embodiments, the heat treatment involves heating to 600–1200°C (e.g., 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, or 10°C / min) at a heating rate of 4–10°C / min (e.g., 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, or 1200°C) and holding at that temperature for 1.5–3.5 hours (e.g., 1.5 hours, 2 hours, 2.5 hours, 3 hours, or 3.5 hours). The atmosphere for the heat treatment of this invention can be air, vacuum, or an inert gas atmosphere.

[0052] If the heating rate of the heat treatment process in this invention is too low, the amorphous zirconium dioxide will absorb enough energy during the heating process to provide the driving force for its transformation into the crystalline phase, which will eventually lead to changes in the aerogel structure.

[0053] In a second aspect, the present invention provides a zirconia aerogel-modified lightweight heat-insulating fiber preform, which is prepared by the preparation method described in the first aspect.

[0054] To more clearly illustrate the technical solution and advantages of the present invention, the present invention will be further described below with reference to embodiments. The present invention does not specifically limit the source of the reagents used in the embodiments and comparative examples; they can be directly purchased or synthesized in-house.

[0055] Example 1

[0056] S1. Mix zirconium oxychloride octahydrate and anhydrous ethanol at a mass ratio of 1:5 and stir for 30 min. Then add acetic acid (40% of the mass of zirconium oxychloride octahydrate) and continue stirring for 15 min. Next, add methyltrimethoxysilane (molar ratio of zirconium oxychloride octahydrate to methyltrimethoxysilane is 1:0.1) and continue stirring for 15 min. Finally, add polyethylene glycol 600 and acetamide dropwise (molar ratio of zirconium oxychloride octahydrate, polyethylene glycol 600 and acetamide is 1:0.5:1) and stir until homogeneous to obtain zirconium dioxide aerogel precursor solution.

[0057] S2. After vacuum impregnating the carbon fiber needled preform in a zirconia aerogel precursor solution for 30 min, urea (the molar ratio of zirconium oxychloride octahydrate to urea is 1:10) is added dropwise and stirred continuously for 10 min. The mixture is then transferred to a container and sealed, and heated at 70 °C for 20 h. After cooling, it is placed in n-hexane and heated at 60 °C for 20 h to complete solvent replacement. Then, it is removed and placed in an 80 °C forced-air drying oven for 15 h. Finally, under vacuum protection, the temperature is raised to 600 °C and held for 2 h to prepare a zirconia aerogel-modified lightweight heat-insulating fiber preform, wherein the ZrO2 shrinks by 5% compared to before drying.

[0058] Example 2

[0059] S1. Mix zirconium oxynitrate and anhydrous ethanol at a mass ratio of 3:5 and stir for 30 min. Then add citric acid (60% of the mass of zirconium oxynitrate) and stir for 10 min. Next, add γ-aminopropyltriethoxysilane (the molar ratio of zirconium oxychloride octahydrate and γ-aminopropyltriethoxysilane is 2:0.5) and continue stirring for 15 min. Finally, add polyethylene glycol 400 and N,N-dimethylformamide dropwise (the molar ratio of zirconium oxynitrate, polyethylene glycol 400 and N,N-dimethylformamide is 2:0.1:0.5) and stir until homogeneous to obtain the zirconium dioxide aerogel precursor solution.

[0060] S2. After impregnating the quartz fiber needled preform in a zirconium dioxide aerogel precursor solution under normal pressure for 60 min, urea (molar ratio of zirconium oxynitrate and urea is 1:5) is added dropwise and stirred continuously for 10 min. The mixture is then transferred to a container and sealed, heated at 90℃ for 10 h, cooled, placed in n-heptane, and heated at 70℃ for 40 h to complete solvent replacement. The preform is then removed and placed in a 120℃ forced-air drying oven for 10 h. Finally, under nitrogen atmosphere protection, the temperature is raised to 1000℃ and held for 1.5 h to prepare a zirconium dioxide aerogel-modified lightweight heat-insulating fiber preform, wherein the ZrO2 shrinks by 4% compared to before drying.

[0061] Example 3

[0062] S1. Mix zirconium butoxide and ethylene glycol at a mass ratio of 5:10 and stir for 30 min. Then add a mixed solution of sodium hydroxide and hydrochloric acid (60% of the mass of zirconium butoxide, wherein the mass ratio of hydrochloric acid, sodium hydroxide and deionized water is 5:1:50) and continue stirring for 15 min. Then add γ-glycidoxypropyltrimethoxysilane (the molar ratio of zirconium butoxide and γ-glycidoxypropyltrimethoxysilane is 5:1) and continue stirring for 15 min. Finally, add polyethylene glycol 800 and oxalic acid dropwise (the molar ratio of zirconium butoxide, polyethylene glycol 800 and oxalic acid is 2:0.5:0.5) and stir until homogeneous to obtain the zirconium dioxide aerogel precursor solution.

[0063] S2. After vacuum impregnating the carbon fiber needled preform in a zirconia aerogel precursor solution for 30 min, citric acid (molar ratio of zirconium butoxide to citric acid is 1:5) is added dropwise and stirred continuously for 10 min. The mixture is then transferred to a container and sealed, heated at 70 °C for 20 h, cooled, placed in n-pentane, and heated at 30 °C for 20 h to complete solvent replacement. The preform is then removed and placed in a 100 °C forced-air drying oven for 10 h. Finally, under vacuum protection, the temperature is raised to 1200 °C and held for 2 h to prepare a zirconia aerogel-modified lightweight heat-insulating fiber preform, in which ZrO2 shrinks by 7% compared to before drying.

[0064] Table 1. Performance comparison of fiber preforms before and after modification in Examples 1-3 of the present invention.

[0065]

[0066] As shown in Table 1, compared with the unmodified fiber preform, the density of the modified fiber preform in this embodiment of the invention increases by no more than 32%, and the room temperature thermal conductivity does not change significantly.

[0067] Comparative Example 1

[0068] It is basically the same as Example 1, except that in step S1, the molar ratio of zirconium oxychloride octahydrate and methyltrimethoxysilane is 1:5.

[0069] The inventors discovered that the final product is a fiber preform modified with ZrO2-SiO2 composite aerogel. Because the ZrO2 aerogel and SiO2 aerogel are formed separately, the skeletons after forming are "entangled" with each other. However, there are significant differences in their physical properties, which can lead to structural damage at high temperatures.

[0070] Comparative Example 2

[0071] It is basically the same as Example 1, except that methyltrimethoxysilane is not added in step S1.

[0072] The inventors discovered that after vacuum impregnating the carbon fiber needled preform in a zirconium dioxide aerogel precursor solution for 30 minutes, adding urea (the molar ratio of zirconium oxychloride octahydrate to urea is 1:10) and stirring continuously for 10 minutes, transferring it to a container and sealing it, and heating it at 70°C for 20 hours, it remained in a solution state and could not gel.

[0073] Comparative Example 3

[0074] It is basically the same as Example 1, except that in step S1, the molar ratio of zirconium oxychloride octahydrate and methyltrimethoxysilane is 1:0.05.

[0075] The inventors discovered that after vacuum impregnating the carbon fiber needled preform in a zirconium dioxide aerogel precursor solution for 30 minutes, adding urea (the molar ratio of zirconium oxychloride octahydrate to urea is 1:10) and stirring continuously for 10 minutes, transferring it to a container and sealing it, and heating it at 70°C for 20 hours, it remained in a solution state and could not gel.

[0076] Comparative Example 4

[0077] It is basically the same as Example 1, except that acetamide is not added in step S1.

[0078] The inventors discovered that after solvent replacement and drying, ZrO2 shrinks by 73% compared to before drying, and cannot maintain an intact aerogel structure.

[0079] Comparative Example 5

[0080] It is basically the same as Example 1, except that polyethylene glycol 600 is not added in step S1.

[0081] The inventors discovered that after solvent replacement and drying, ZrO2 shrinks by 69% compared to before drying, and cannot maintain an intact aerogel structure.

[0082] Comparative Example 6

[0083] It is basically the same as Example 1, except that in step S1, after cooling, anhydrous ethanol is used for solvent replacement.

[0084] The inventors discovered that after solvent replacement and drying, ZrO2 shrinks by 83% compared to before drying, and cannot maintain an intact aerogel structure.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.

Claims

1. A method for preparing a lightweight heat-insulating fiber preform modified with zirconium oxide aerogel, characterized in that: The preparation method comprises the following steps: A zirconium compound, a solvent, a pH regulator, a cross-linking agent, a pore structure control agent and a drying control agent are mixed to obtain a zirconium dioxide aerogel precursor solution; the cross-linking agent is a silane coupling agent cross-linking agent; the pore structure control agent is polyethylene glycol; the drying control agent is one or more of acetamide, N,N-dimethylformamide, ethylene glycol and oxalic acid; the molar ratio of the cross-linking agent to the zirconium compound is 0.1-0.25:1; the molar ratio of the pore structure control agent to the zirconium compound is 0.1-0.5:1-5; the molar ratio of the drying control agent to the zirconium compound is 0.1-1:1-5; The fiber preform is immersed in the zirconium dioxide aerogel precursor solution and a gel accelerator is added, and a zirconium oxide aerogel-modified lightweight heat-insulating fiber preform is obtained through gel reaction, solvent replacement, drying and heat treatment; the replacement solvent of the solvent replacement is a liquid alkane; the gel accelerator is one or more of polyacrylic acid, urea and citric acid; and the molar ratio of the gel accelerator to the zirconium compound is 1 to 10:

1.

2. The preparation method according to claim 1, characterized in that: The zirconium compound is one or more of zirconium oxychloride octahydrate, zirconium oxynitrate, zirconium n-butoxide, zirconium tetrachloride and zirconium polyacetylacetonate; The mass ratio of the solvent to the zirconium compound is 5-10:1-5; and / or The pH regulator is used in an amount of 40-60% of the mass of the zirconium compound.

3. The preparation method according to claim 2, characterized in that: The solvent is an alcohol; and / or The pH adjuster is an organic weak acid or a mixture of an inorganic acid and an alkaline substance.

4. The preparation method according to claim 3, characterized in that: The solvent is one or more of anhydrous ethanol, propanol, methanol and ethylene glycol.

5. The preparation method according to claim 1, characterized in that: The crosslinking agent is one or more of methyltrimethoxysilane, dimethyldiethoxysilane, γ-aminopropyltriethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.

6. The preparation method according to claim 1, characterized in that: The pore structure control agent is one or more of polyethylene glycol 400, polyethylene glycol 600 and polyethylene glycol 1000.

7. The preparation method according to claim 1, characterized in that: The fiber preform adopts one or more of carbon fiber, quartz fiber, glass fiber, mullite fiber and phenolic fiber; and / or The fiber preform is one or more of a continuous fiber needle-punched structure, a web structure, a 2.5D woven structure, and a three-dimensional woven structure.

8. The preparation method according to claim 1, characterized in that: The temperature of the gel reaction is 60-90° C.; and / or The temperature of the solvent replacement is not higher than the boiling point of the liquid alkane.

9. The preparation method according to claim 1, characterized in that: The boiling point of the liquid alkane is not higher than 100°C.

10. The preparation method according to claim 1, characterized in that: The drying is one or more of normal pressure drying and supercritical drying; and / or The heat treatment is performed by heating the temperature to 600-1200° C. at a heating rate of 4-10° C. / min and keeping the temperature for 1.5-3.5 hours.

11. A lightweight heat-insulating fiber preform modified by zirconium oxide aerogel, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Preparation method of fiber / ZrO2 aerogel composite material

    CN102503355A

  • Method for preparing metal oxide aerogel by taking inorganic salt as raw material

    CN104772084A

  • Preparation method of high-temperature-resistant modified ZrO2-SiO2 composite aerogel

    CN115784242A